Reconsidering Distributions: A Critical Analysis of the Regulation of Distributions to Shareholders in the Companies Act of 2008, with Special Reference to the Solvency and Liquidity Requirement - Van der Merwe, Constant Pieter (Stellenbosch : Stellenbosch University, 2015)
Thesis (LLM)--Stellenbosch University, 2015